1999
DOI: 10.1074/jbc.274.36.25583
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of Guanylyl Cyclase-activating Protein and a Mechanism of Photoreceptor Guanylyl Cyclase Activation

Abstract: 2؉ . Additional mutation that restores normal activity of the GCAP-2 chimera mutant also restores its ability to dimerize in the absence of Ca 2؉ . These results suggest that dimerization of GCAP-2 can be a part of the mechanism by which GCAP-2 regulates the photoreceptor guanylyl cyclase. The Ca 2؉ -free GCAP-1 is also capable of dimerization in the absence of Ca 2؉ , but unlike GCAP-2, dimerization of GCAP-1 is resistant to the presence of Ca 2؉

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 41 publications
(57 reference statements)
4
75
1
Order By: Relevance
“…Recent studies show that the catalysis of the cyclic GMP formation by ROS-GC1 occurs at a dimer interface (52) and that its activation by GCAPs or S100 involves dimerization step (29,30). Thus, ROS-GC1 requires dimerization for effective catalytic activity (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies show that the catalysis of the cyclic GMP formation by ROS-GC1 occurs at a dimer interface (52) and that its activation by GCAPs or S100 involves dimerization step (29,30). Thus, ROS-GC1 requires dimerization for effective catalytic activity (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the results presented above indicate that under all tested experimental conditions, the amount of cyclic GMP formed by the ERTfDCM mutant is lower than that formed by wt-rROS-GC1. Earlier studies have indicated that the active state of ROS-GC1 is represented by its dimeric form (29,30). To determine if the impaired functioning of the cyclase is a result of disturbed dimer formation, the dimerization of the wt and mutated ROS-GC1 was tested by crosslinking and gel-filtration chromatography.…”
Section: Hek293 and Cos Cells Expression Systems Are Comparable It Wmentioning
confidence: 99%
See 1 more Smart Citation
“…7B) was modeled on the basis of the crystal structure of Ca 2ϩ -bound neurocalcin (1BJF), which is the closest available structure of a Ca 2ϩ -bound NCS protein dimer that has highest sequence identity to VILIP-1. Ca 2ϩ -bound neurocalcin forms a dimer in solution (54), and the crystal structure of the Ca 2ϩ -bound dimer (26) specifies intermolecular contacts primarily between residues in the N-terminal domain (EF1 and EF2) and exposed residues in EF3. Our chimera analysis above on VILIP-1 precludes any intermolecular dimer contacts involving residues in EF1, EF2, and EF3 (i.e.…”
Section: Two-dimensionalmentioning
confidence: 99%
“…The dimerization and activation of GC-E are abolished in a GCAPdepleted membrane preparation of the retina, and added recombinant constitutively active mutants of GCAP-1 and GCAP-2 cause dimerization and high activity of GC-E even at high Ca2+ concentrations (> 1 tcM) [145]. GCAP-2 dimerization caused by decrease of the intracellular Ca2+ concentration is also reported, and it is suggested that the dimerization of GCAPs might be a mechanism for the GC-E and GC-F activation [145,146].…”
Section: Regulation Of Guanylyl Cyclases By Associated Proteinsmentioning
confidence: 99%